NeuroAid II (MLC901) and polypharmacy in stroke and the risk of hepatotoxicity: a case report - Abdul Rashid, Anna Misya’il; Md Noh, Mohamad Syafeeq Faeez; Yusof Khan, Abdul Hanif Khan; Wei, Chao Loh; Baharin, Janudin; Ibrahim, Azliza; Inche Mat, Liyana Najwa; Wan Sulaiman, Wan Aliaa; Fan, Kee Hoo; Hanapiah, Fazah Akhtar; Basri, Hamidon (SpringerOpen, 2021)
Background: NeuroAid II (MLC901) is a promising therapy for stroke patients who present outside of therapeutic window for reperfusion therapy. Studies have proven its efcacy in ischemic stroke; however, data of drug safety and combination with other medications especially anticoagulants are heterogenous. We report a possible case of hepatotoxicity induced by NeuroAid II in combination with anticoagulants. Case presentation: We report an elderly patient who developed symptoms of cardioembolic stroke presented outside of time window for reperfusion therapy. He was started on a regiment of statins, anticoagulation, beta blockers and NeuroAid II. One month later he presented with deranged liver enzymes. Cessation of NeuroAid II resulted in rapid improvement of transaminitis within days. Conclusions: We wish to highlight the potential harmful efect of administering NeuroAid II with an anticoagulant and the importance of routine follow-up and blood monitoring in the elderly patients with stroke.